1982
DOI: 10.1177/000348948209100118
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Anatomy of Eustachian Tube and Middle Ear Cavity in Animal Models for Otitis Media

Abstract: The comparative anatomy of the normal eustachian tube (ET) and normal middle ear cavity of three animal species (rat, gerbil, and chinchilla) is described relating to the usefulness of these animals as models for otitis media (OM). Routine histological and anatomical techniques and procedures were used. The gerbil and chinchilla, although of different sizes, are quite similar, having hypertrophied middle ear bullae, nearly vertical ET, and similar histology including seromucous glands draining directly into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 19 publications
0
23
1
Order By: Relevance
“…Several observations have shown that the middle-ear mucosa is covered by ciliated epithelium mixed with nonciliated secretory cells, both in man and in animal models [2][3][4][5][6][11][12][13][14][15][16]. Graves and Edwards [17] noted that the lower half of the tube was covered by ciliated cells while the upper part was covered by non-ciliated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several observations have shown that the middle-ear mucosa is covered by ciliated epithelium mixed with nonciliated secretory cells, both in man and in animal models [2][3][4][5][6][11][12][13][14][15][16]. Graves and Edwards [17] noted that the lower half of the tube was covered by ciliated cells while the upper part was covered by non-ciliated cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the bone at the top of the bulla is very thin, allowing injection of an experimental preparation directly into the middle ear by this route with little trauma to the animal. From a bacteriologic susceptibility standpoint, otitis media is readily induced in the chinchilla after a transbullar bacterial injection of nontypable H. influenzae or S. pneumoniae, but the chinchilla is not naturally susceptible to otitis, unlike other rodent animal models such as the rabbit, guinea pig [17] and the rat [18]. Researchers can thus be reasonably certain that the observed disease is a consequence of experimental manipulation.…”
Section: Models For Investigation Of Otitis Mediamentioning
confidence: 99%
“…Indeed, this rodent features an auditory spectrum rather similar to the human's hearing, with good low frequency hearing (Lay, 1972;Müller, 1996;Ryan, 1976;Suberman et al, 2011;Vater and K€ ossl, 2011). In rodents, the middle and inner ears are included in the tympanic bulla (Bulla tympanica, or auditory bulla) that is naturally hypertrophic in gerbils (Bergin et al, 2013;Daniel et al, 1982;Lay, 1972;Mason, 2016). Furthermore, gerbils rarely present with acute otitis media (Bergin et al, 2013;Daniel et al, 1982) which eases the assessment of noninfectious middle ear surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, the middle and inner ears are included in the tympanic bulla (Bulla tympanica, or auditory bulla) that is naturally hypertrophic in gerbils (Bergin et al, 2013;Daniel et al, 1982;Lay, 1972;Mason, 2016). Furthermore, gerbils rarely present with acute otitis media (Bergin et al, 2013;Daniel et al, 1982) which eases the assessment of noninfectious middle ear surgery.…”
Section: Introductionmentioning
confidence: 99%